Comparison of the Streptococcus mutans colony count changes in plaque following chlorhexidine (0.12%) mouth rinse and green tea extract (0.5%) mouth rinse in 8-12-year-old children - Shamika Kamath; Rahul Hegde; Narayana Kamath (Wolters Kluwer Medknow Publications, 2021)
Background: Mouth rinses are solutions or liquids used to rinse the mouth to have a therapeutic effect by relieving infection or preventing dental caries due to their antimicrobial properties. Aims: This study was carried out to compare the effect of 0.12% chlorhexidine mouth rinse and 0.5% green tea extract mouth rinse on the colony-forming units (CFUs) of Streptococcus mutans in plaque in children. Materials and Methods: The sample for the study consisted of fifty schoolchildren aged 8-12 years with four or more (decay component) of decayed, missing, and filled teeth index. Children were divided randomly into two groups and were asked to rinse with the prescribed mouth rinse twice daily for 2 weeks under supervision. The plaque samples were collected at baseline (prerinsing) and postrinsing and tested for the CFUs of S. mutans. Results: The results of the study indicate that there was a statistically significant reduction (pre- and postrinsing) in S. mutans colony count in both the study groups. There was no statistically significant difference in the reduction of S. mutans colony count between 0.12% chlorhexidine mouth rinse group and 0.5% green tea mouth rinse group. Conclusion: Green tea mouth rinse is effective against S. mutans - one of the major dental plaque microorganisms.